When and how do professional soccer players experience maximal intensity sprints in LaLiga? - Oliva-Lorenzo, J. M.; Fortes, V.; López-Del Campo, R.; Resta, R.; Muyor, J. M. (Science and Medicine in Football, 2023)
Objectives: To 1) examine the periods in which maximal intensity sprints occurred during professional soccer matches and 2) analyze the maximal intensity sprints registered in match play considering the effect of playing position and other contextual variables. Methods: A total of 1252 match observations were collected from 277 male professional players. Sprinting actions at maximal intensity were analyzed during 30 matches, and both contextual and performance variables were collected using performance tracking systems. Results: Maximal intensity sprints were more frequent in the first and last periods of the match (0`-15`; 75`-90`), regardless of the playing position (?2=23.01; p=0.29; ES=0.07). These sprints were usually non-linear actions without possession of the ball and had different tactical purposes depending on the position. The mean sprint duration ranged from ~4.9 s to ~9 s, the mean distance covered ranged from ~30 m to ~55 m, while the mean maximum velocity was between ~30.12 and ~32.80 km/h depending on the tactical purpose and playing position. Conclusion: Professional soccer players need to be prepared during warm-ups for maximal intensity sprints in the first period of the match as well as maximal intensity sprints under high fatigue conditions given the frequency of sprints in the last period of the match. Also, training drills should be designed with a special focus on non-linear sprints without possession of the ball, based on the main tactical purpose of each position (e.g., CD: interceptions; MF: recovery runs; FB, WMF and FW: run the channel).